Two-way differential strategy for wireless sensor networks - Alabed, Samer; Alsaraira, Amer; Mostafa, Nour; Al-Rabayah, Mohammad; Shdefat, Ahmed; Zaki, Chamseddine; A. Saraereh, Omar; Al-Arnaout, Zakwan (Bulletin of Electrical Engineering and Informatics, 2023)
In this paper, a novel optimal two-way amplify and forward (AF) differential beamforming method for wireless sensor network is proposed. The proposed method is an advanced signal processing technique used to enhance the performance and reliability of the communication link by exploiting the diversity provided by multiple antennas. Unlike current state-of-the-art methods which require the knowledge of channel state information (CSI) at both transmitting and receiving antennas or at least at the receiving antennas, the suggested method does not need CSI at any transmitting or receiving antenna. Moreover, the proposed method enjoys high error performance with high diversity and coding gain and has a very low encoding and decoding complexity. Through our simulations, the proposed method is proved to outperform the best known non-coherent multi-antenna methods.